2020
DOI: 10.3390/jcm9010187
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Airway Inflammation in Preschoolers with Asthma—Results of a Two-Year Longitudinal Study

Abstract: Fractional exhaled nitric oxide (FeNO) is a non-invasive marker for eosinophilic airway inflammation and has been used for monitoring asthma. Here, we assess the characteristics of FeNO from preschool to school age, in parallel with asthma activity. A total of 167 asthmatic children and 66 healthy, age-matched controls were included in the 2-year prospective PreDicta study evaluating wheeze/asthma persistence in preschool-aged children. Information on asthma/rhinitis activity, infections and atopy was recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…The “Post‐infectious immune reprogramming and its association with persistence and chronicity of respiratory allergic diseases” (PreDicta) study was designed to prospectively evaluate asthma persistence in preschoolers in association with microbial exposures and immunological responses 26 . PreDicta has demonstrated differential immune responses to viruses in asthma, 27,28 as well as evolution of airway inflammation at that age 29 …”
Section: Introductionmentioning
confidence: 99%
“…The “Post‐infectious immune reprogramming and its association with persistence and chronicity of respiratory allergic diseases” (PreDicta) study was designed to prospectively evaluate asthma persistence in preschoolers in association with microbial exposures and immunological responses 26 . PreDicta has demonstrated differential immune responses to viruses in asthma, 27,28 as well as evolution of airway inflammation at that age 29 …”
Section: Introductionmentioning
confidence: 99%
“…Children aged 3-5 years with asthma may exhibit noneosinophilic inflammation. Additionally, Xepapadak and other demonstrated that FeNO level can be elevated with time and age (13). The difference in results between the two age groups could also be attributed to different FeNO detection methods and difficulty controlling the degree of cooperation by younger children.…”
Section: Discussionmentioning
confidence: 97%
“…A detailed understanding of the tissue-specific immune landscape in health and disease is required to improve the clinical management of many childhood diseases. Aberrant inflammation is a hallmark of several childhood lung diseases, including bronchopulmonary dysplasia (Balany and Bhandari, 2015), preschool wheeze (Xepapadaki et al, 2020), asthma (Chedevergne et al, 2000), cystic fibrosis (Tirouvanziam et al, 2000), primary ciliary dyskinesia (Cockx et al, 2017), and COVID-19 (Neeland et al, 2021). Despite this, little is known regarding the immune cell profiles and mechanisms governing inflammatory processes in the early life respiratory system.…”
Section: Introductionmentioning
confidence: 99%